KUALITAS NUTRISI AMPAS SAGU HASIL FERMENTASI JAMUR TIRAM PUTIH (Pleurotus ostreatus) DENGAN WAKTU PANEN YANG BERBEDA - Insun Sangadji (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2019)
Improving local feedstuff which is abundantly available in Maluku Province suh as sago (Metroxylon rumphii) by-product to be a nutritional feedstuff for live is an innovative way to address the scarcity of nutritious feed for livestock in Maluku. The purpose of this research was arranged into a complete randomized design with four treatments: control (no fermentation), before harvest (after full mycelium), the first harvest, and the second harvest. Each treatment was replicated triple. Least square test was applied to determine the statistical differences among the treatmenst. The observed variables were dry matter, crude protein, Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF) and lignin. The result showed that there were significant differences (P<0.05) on dry matter content, protein content, NDF, ADF and lignin content among treatments. Average dry matter content in each treatment was 40.08%, 35.16%, 28,78% and 27,23% for control, before harvest, the second harvest and the first harvest, respectively. Avarage protein content in each treatment was 5.52%, 5.33%, 5.21% and 2.05% for before harvest, the first harvest, the second harvest and control, respectively. Avarage NDF content in each treatment was 55.59%, 51.21%, 48.73% and 46.43% for control, before harvest, the first harvest and the second harvest, respectively. Average ADF content in each treatment was 46.53%, 44.57%, 43.74% and 42.13% for control, before harvest, the secobd harvest and the first harvest, respectively. Average lignin content in each treatment was 5.63%,4.37%, 3.29% and 3.21% for control, before harvest, the second harvest and the first harvesst, respectively. Based on nutrient content, it is suggested that fermented sago by-product on the first harvest time can be applied as livestock feedstuff. However, fermented sago by-product on the second harvest time is economical.